Deliberate practice in emotion-focused therapy - Goldman, Rhonda N.; Vaz, Alexandre; Rousmaniere, Tony (Essentials of deliberate practice series, 2021)
"This book presents deliberate practice exercises in which students and trainees rehearse fundamental emotion-focused therapy (EFT) skills to develop basic competence and hone their own personal therapeutic style. Each exercise consists of role-playing scenarios in which two trainees act as a client and a therapist, switching back and forth under the guidance of a supervisor. The trainee playing the therapist improvises appropriate and authentic responses to a series of client statements organized into three difficulty levels-beginner, intermediate, and advanced-that reflect common problems and concerns encountered by EFT practitioners. The first 12 exercises each focus on a single skill, such as responding empathically to clients, exploring emotions, building therapist self-awareness, recognizing client markers, and repairing relationship ruptures. These are followed by two comprehensive exercises-an annotated transcript and free-form mock therapy sessions-in which trainees integrate these essential skills into a single EFT session. Step-by-step instructions guide participants through the exercises, identify criteria for mastering each skill, and explain how to monitor and adjust difficulty. Guidelines to help trainers and trainees get the most out of training are also provided"--